Gestão de equipes remotas - Cunha, Ricardo Netto (Universidade do Vale do Rio dos Sinos, 2012)
The current paper adresses the issue of remote team management through a descriptive exploratory research conducted in a company from technology área. Data were collected through interviews in person and by e-mail. Leading people is a task that requires experience and sensitivity. This task becomes more difficult as the physical distance between offices requires the leader to manage the team without having a physical presence frequently. These concepts were explored in the survey and compared with theory analyzed resulting in the proposition of management rules for remote teams. The results show that remote team managers must be prepared and develop some skills that are critical in managing remote teams, especially communication. In addition, managers of remote teams need to understand the new requirements of the model checking that is highly beneficial, cost-effective and can generate many benefits to the companies.
Keywords: Equipes Remotas; Gestão; TI; Liderança; Management; Leadership